PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF PLASMA CLUSTER UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS VIIIC SMP NEGERI 2 PONOROGO - Nurfarida, Hanna; Susilo, Herawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Based on observations and interviews of the implementation of science lesson in the SMP 2 Ponorogo, it was obtained that the learning strategy is teacher-centered, with dominant learning methods are lecture, discussion, and question-and-answer. The teacher was not giving the opportunity to students to develop thinking in finding the concept,  less interaction among students and between students and teacher, low student activity and more than 60% of students have not reached the specified school’s KKM. The implementation of plasma cluster cooperative learning strategy (PCCLS) is expected to increase students' activities and cognitive science learning outcomes. Classroom Action Research (CAR) was carried out in 3 cycles, with 3 stages: planning; implementation and observation; and reflection. At each meeting in the implementation phase, the  PCCLS was implemented with lesson study pattern. The implementation was conducted in class VIII-C (special gym-class) SMPN2 Ponorogo with 32 students, 21 males and 11 females  in 2013/2014. The results showed that the application of PCCLS can enhance the students’ activities and cognitive science learning outcomes. It was concluded that the implementation of PCCLS can enhance the eight grade students’activities and cognitive learning outcomes. By learning the plasma cluster it will be student-centered and cooperative learning, students are active and creative, which in turn can more easily understand the material. It is recommended that teachers implement variations of classroom instructional strategies, one of which is plasma cluster cooperative learning strategies (PCCLS). Keywords : Cooperative Strategy, Plasma Cluster, Activity,  Learning Outcomes, Cognitive